Civic Seoul 2030: toward infrastructural renaturalization - Canessa, Nicola Valentino; Gausa , Manuel; Hae-Won , Shin (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Citizens play a crucial role in shaping cities, balancing rights and responsibilities in public and private spaces. The concept of civic ethics involves finding a common identity within diverse individual differences and promoting sustainable urban ecosystems. Despite economic growth and formal democracy, residents of Seoul may not yet fully embrace this civic identity. Civic ethics call for a more integrated approach to city living, emphasizing values such as autonomy, empathy, diversity, and ecological awareness. Seoul’s future development will be influenced by global trends in urbanization, requiring the city to adapt and plan strategically. The Metropolitan Government of Seoul is focused on inclusive growth, developing new engines for growth, and responding to changing demographics, but simultaneously on a process of decarbonization and renaturalization. To create a vision for ’Future Seoul,’ the city is analyzing successful urban strategies from around the world and considering innovative approaches like a ’Civic City Seoul’ model. In the light of a series of preliminary research, a number of architects are invited for our ‘Underground’ and ‘Superground’ projects. These projects reexamine various urban systems which used to be regarded as monofunctional and with a strong characterization related to urban renaturalization processes.